ATLAS2030 Pediatric Gait Exoskeleton: Changes on Range of Motion, Strength and Spasticity in Children With Cerebral Palsy. A Case Series Study - Delgado, Elena; Cumplido, Carlos; Ramos, Jaime; Garcés, Elena; Puyuelo, Gonzalo; Plaza, Alberto; Hernández, Mar; Gutiérrez, Alba; Taverner, Thomas; Destarac, Marie André; Martínez, Mercedes; García, Elena (Frontiers in Pediatrics, 2021)
Background: Cerebral Palsy (CP), the most common motor disability in childhood, affects individual's motor skills, movement and posture. This results in limited activity and a low social participation. The ATLAS2030 exoskeleton is a pediatric device that enables gait rehabilitation for children with neurological or neuromuscular pathologies with gait pathology. Purpose: To study changes in relation to range of motion (ROM), strength and spasticity in children with CP after using the ATLAS2030 gait exoskeleton. Methods and Participants: Three children (mean age 8.0 ± 2.0), two girls and one boy, two of them with GMFCS IV and one with GMFCS III, received robot-assisted gait training (RAGT) with ATLAS2030 for one month. Results: The average time of exoskeleton use was 54.7 ± 10.4 min in all sessions, and all participants were able to perform all exercises. The strength of all muscle groups was increased after the 10 sessions for the participants assessed and the limited ROM in the sagittal plane (hip and knee extension and ankle dorsiflexion) decreased after the use of the exoskeleton compared to the initial state. Spasticity was reduced at the end of the sessions after the use of the exoskeleton compared to their initial state. Conclusion: The ROM, spasticity and strength were improved after RAGT with ATLAS2030 exoskeleton in these children with CP. However, further studies with larger samples should be carried out to confirm our findings.